Russian Law-Making (on the Example of the Federal Executive Authority): Ethical Aspect - K. S. Litovko (Теоретическая и прикладная юриспруденция)
The purpose of the work was to analyze the modern process of law-making in Russia on the example of the federal executive authority, taking into account ethical aspects. To achieve this goal, general philosophical methods and the formal legal method were used. The paper presented current theoretical views on law-making, as well as described the procedure of law-making in the federal executive authority. Ethical contradictions and problems existing in this procedure were considered. The general trends in the development of the law-making process in Russia were also indicated and conclusions were drawn about the need to take into account ethical approaches when improving the law-making procedure.